Modification of amphipathic non-opioid dynorphin A analogues for rat brain bradykinin receptors. Issue 1 (1st January 2015) - Lee, Yeon Sun; Hall, Sara M.; Ramos-Colon, Cyf; Remesic, Michael; LeBaron, Lindsay; Nguyen, Ann; Rankin, David; Porreca, Frank; Lai, Josephine; Hruby, Victor J.
Graphical abstract: Abstract: It has been shown that under chronic pain or nerve injury conditions, up-regulated dynorphin A (Dyn A) interacts with bradykinin receptors (BRs) to cause hyperalgesia in the spinal cord. Thus BRs antagonist can modulate hyperalgesia by blocking Dyn A's interaction with the BRs in the central nervous system. In our earlier structure–activity relationship (SAR) study, [des-Arg 7 ]-Dyn A-(4–11)13 was discovered as a minimum pharmacophore for rat brain BRs with its antagonist activity (anti-hyperalgesic effect) in in vivo tests using naïve or injured animals. We have pursued further modification on the [des-Arg 7 ]-Dyn A analogues and identified a key insight into the pharmacophore of the rat brain BRs: amphipathicity.